2002
DOI: 10.1021/cm0112183
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Ultraflat Titanium Oxide Surfaces

Abstract: In this work we investigated the physical and chemical nature of ultraflat titanium dioxide (TiO2) samples which we had previously used as substrates for the investigation of adsorbed protein molecules (Cacciafesta, P.; Humphris, A. D. L.; Jandt, K. D.; Miles, M. J. Langmuir 2000, 16, 8167). Titanium films were prepared by thermal evaporation on a heated mica surface and either separated from the mica to investigate the resulting surface or left in contact with the mica to analyze the titanium−mica interface. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
28
1
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 47 publications
4
28
1
1
Order By: Relevance
“…The concentration of the hydrocarbon layer was abruptly decreased after Ar sputtering, which indicates that its source probably was due to adsorption of carbon compounds from the ambient air, and was mainly located on the oxide surface. This degree of contamination is conformal to the percentages found after a common process of surface cleaning 32 .…”
Section: Xps Analysissupporting
confidence: 52%
“…The concentration of the hydrocarbon layer was abruptly decreased after Ar sputtering, which indicates that its source probably was due to adsorption of carbon compounds from the ambient air, and was mainly located on the oxide surface. This degree of contamination is conformal to the percentages found after a common process of surface cleaning 32 .…”
Section: Xps Analysissupporting
confidence: 52%
“…So the observation of these hexagonal diffraction spots reveals that these single crystals are related to a new phase different from those of TiO 2 . It has been documented that titanium (III) oxide has a hexagonal structure [13,14] and in our previous work [15,16] we have reported that, during the photo-assisted sol-gel process, the UV light introduced promotes the reduction of Ti (IV) into Ti (III). So it can be concluded that the newly formed phase is Ti 2 O 3 single crystal; just the introduction of the UV illumination on colloids has resulted in the formation of a binary TiO 2 -Ti 2 O 3 composite.…”
Section: Resultsmentioning
confidence: 76%
“…[76] Crystalline as well as disordered surface areas of these titanium films where observed by AFM, the former with atomic resolution. Ultra-flat titanium (TiO 2 ) thin films like this are of particular interest as model systems for molecular resolved protein adsorption studies [65,76] with AFM since they combine the chemical properties of a clinically used biomaterial (TiO 2 ) with the flatness required for high resolution AFM investigations.…”
Section: Two-dimensional Biomaterialsmentioning
confidence: 96%